Los yacimientos olvidados : registro y musealización de campos de batalla - Galán, Mario Ramírez (Archaeopress Publishing Ltd, 2017)
This text shows the great potential of Spanish battlefields and their heritage for archaeological study. It suggests Spain could be regarded as a very important country regarding battlefield archaeology.